Research of Weft Insertion Mechanism Design of Carbon Fiber Multilayer Loom with Considering the Gear Dynamic Meshing Force - Li Hao; Yang Jiancheng; Jiang Xiuming (Jixie chuandong)
In view of the poor stability and remarkably rapier vibration of the existing weft insertion mechanism of carbon fiber multilayer loom which result from rapier motion acceleration volatility. Through increasing one more meshing gear and setting appropriate phase differences between the gears combining with reducing the module of the meshing gears,the dynamic characteristics of the mechanism are improved effectively. Using the MSC- ADAMS software,the different module,different number of gears and different phrase between gears meshing with rack are simulated and analyzed. The simulation shows that by changing the form of two same phrase gear transmission into the form of two different phrase gear transmission,the dynamic performance can be improved somehow,but it’s not effectively in case of relatively large module. The presented method is effectively improving the dynamic stability of the mechanism. The amplitude of the acceleration at each frequency is reduced by an average of 25%.